(untitled) (Observatorio Económico, 2013)
Perhaps the two main issues in the debate on higher education in Chile in recent years are financing and quality, above all the former, on which proposals have been put forward to make higher education accessible free of charge. This article focuses instead on aspects of university quality, because, beyond who pays, or even if higher education were entirely free of charge, what kind of education will be provided and how will it contribute to reducing inequality? Continue reading...